99 5 Year Experience of Tavi Implantation: Patient Characteristics, Morbidity and Mortality. (31st May 2014) - Augustine, Daniel; Carpenter, Alex; Wilson, Catherine; Baumbach, Andreas; Turner, Mark; Townsend, Mandie
Abstract : Aims: To define the characteristics of a real world population treated with transcatheter aortic valve implantation (TAVI) in a tertiary hospital and to evaluateclinical outcome. This includes in hospital morbidity rates and a comparison of 30 day, 1 year and 2 year mortality rates with those of the UK TAVI registry. We also present 3 year mortality data which to date has not been evaluated from the UK TAVI registry. Methods: The Bristol Heart Institute TAVI database was created to record procedural details and outcomes. Data was analysed on 144 consecutive patients undergoing TAVI between January 2008 and March 2013. Results: Patient characteristics are shown in Table 1. Peak aortic valve gradient (mean ± SD) was 80.7 ± 24.1mmHg. Of note, the mean age at implantation was 83 ± 6 years, 40.1% had undergone previous cardiac surgery, 65.2 % had a creatinine clearance of < 50 ml/min, 31.2% had a left ventriclular ejection fraction (LVEF) of <50% and at the time of implant 63.2% of patients had a NYHA functional class status of III/IV. Diabetes was present in 17.4%. Procedural characteristics are recorded in Table 2. A variety of access routes were used: femoral 77.71%; subclavian 8.3%; trans apical 13% and trans aortic 0.7% (n = 1). Deployment was successful in 95.8% of patients, with the remainder receiving either a second device implant (2.8%) or conversion to open surgery (1.4%). Immediately post deployment there was ≥ moderate paravalvar AR in 12.3% of patients (vs. 13.6% UK TAVI registry) although this improved to 2.7 % during follow up imaging. Major vascular complication rate was 3.4% (vs. 6.3% UK TAVI registry). In hospital permanent pacemaker rate was 18.7 % (vs. 16.3% UK TAVI registry) and the incidence of stroke was 2.7% (vs. 4.1% UK TAVI registry). Mortality rate (vs. UK TAVI registry data) at 30 days was 6.1% (vs. 7.1%); 1 year was 15.2% (vs. 21.4%) and 2 years was 22.7% (vs. 26.3%). Our 3 year mortality rate is 28.7%. Conclusions: Previous studies have shown that significant para prosthetic AR is associated with worse outcome and higher mortality rates. Post implantation paraprosthetic AR is evident in a large proportion of patients (in keeping with previous studies) although with time self expansion of the deviceimproves this. We have shown in this elderly and high risk population that medium term survival is encouraging and favourable when compared with national data. Local auditing of TAVI is important to ensure acceptable morbidity and mortality rates when compared with national ranges and to provide our patients with contemporary information to make an informed decision.